C-terminal low-complexity sequence repeats of Mycobacterium smegmatis Ku modulate DNA binding. Issue 1 (24th January 2013) - Kushwaha, Ambuj K.; Grove, Anne
Abstract : Ku protein is an integral component of the NHEJ (non-homologous end-joining) pathway of DSB (double-strand break) repair. Both eukaryotic and prokaryotic Ku homologues have been characterized and shown to bind DNA ends. A unique feature of Mycobacterium smegmatis Ku is its basic C-terminal tail that contains several lysine-rich low-complexity PAKKA repeats that are absent from homologues encoded by obligate parasitic mycobacteria. Such PAKKA repeats are also characteristic of mycobacterial Hlp (histone-like protein) for which they have been shown to confer the ability to appose DNA ends. Unexpectedly, removal of the lysine-rich extension enhances DNA-binding affinity, but an interaction between DNA and the PAKKA repeats is indicated by the observation that only full-length Ku forms multiple complexes with a short stem-loop-containing DNA previously designed to accommodate only one Ku dimer. The C-terminal extension promotes DNA end-joining by T4 DNA ligase, suggesting that the PAKKA repeats also contribute to efficient end-joining. We suggest that low-complexity lysine-rich sequences have evolved repeatedly to modulate the function of unrelated DNA-binding proteins.